2014
DOI: 10.1103/physrevd.90.083521
|View full text |Cite
|
Sign up to set email alerts
|

Preinflationary genesis with CMB B-mode polarization

Abstract: Recent B-mode polarization observation seems to imply the tensor tilt n T 1 at large angular scale, if the primordial signal is dominated. We show that for a primordial universe, which is in a slowly expanding genesis phase before the slow-roll inflation, the primordial tensor spectrum will get a large-scale cutoff, i.e. n T 1 at large scales while n T ≃ 0 at small scale. We find that this inflationary scenario not only may be consistent with the observation, but also predicts a large-scale anomaly in BB power… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 81 publications
2
39
0
Order By: Relevance
“…In Refs. [29], [30], the preinflationary universe is in a slowly expanding genesis phase with ǫ ≪ −1, which is almost Minkowski space. This genesis phase actually also belongs to the superinflation, but since ǫ ≪ −1, the expansion is actually slow; see also [28] for the emergent universe.…”
Section: A the Superinflationary Phase Before Inflationmentioning
confidence: 99%
See 1 more Smart Citation
“…In Refs. [29], [30], the preinflationary universe is in a slowly expanding genesis phase with ǫ ≪ −1, which is almost Minkowski space. This genesis phase actually also belongs to the superinflation, but since ǫ ≪ −1, the expansion is actually slow; see also [28] for the emergent universe.…”
Section: A the Superinflationary Phase Before Inflationmentioning
confidence: 99%
“…The superinflationary phase before slow-roll inflation may also provide a singular-free realization of inflation, which in the meantime explains the anomalies of the CMB power spectrum [18], [28]; see also [29], [30] for an almost flat pre-inflationary universe.…”
Section: Introductionmentioning
confidence: 99%
“…However, the inflation still suffers from the cosmological singularity problem [1,2], unless it was preceded by a bounce [3][4][5][6][7] or a Genesis phase [8][9][10]. It is exciting to study classical nonsingular cosmology, such as bounce universe models [11,12], Genesis models [13][14][15], slow expansion models [16][17][18][19], since we might get classical nonsingular cosmology without begging the details of the unknown UV-complete gravity theory.…”
Section: Introductionmentioning
confidence: 99%
“…With positive n t , the contribution to C TT ℓ (ℓ < 50) is less than red tensor spectrum, making the model prediction more consistent with the data [12]. It has been shown that once n t is released to be a free parameter in the likelihood analysis, a positive n t is found to be at 3σ confidence level (CL) [10,13].…”
mentioning
confidence: 84%